A new boost type single source seven-level switched-capacitor based inverter with reduced current stress over the components. (July 2022) - Shahsavar, Tala Hemmati; Babaei, Ebrahim; Sabahi, Mehran; khoshkbar-Sadigh, Arash
Abstract: This paper proposes a new single-phase seven-level inverter. The proposed multilevel inverter is based on a Switch-Capacitor (SC) cell and it has the capability to boost the output voltage. This achievement is obtained by a single input voltage source. The main shortcoming of SC networks is the inrush currents passing through the capacitors while being charged. The proposed multilevel inverter overcomes this problem by using a charging-inductor that charges the utilized capacitor smoothly. The performance of the proposed multilevel inverter is described in different operational modes. The power losses of the used components are analyzed. Design guidance to find optimal values of passive components is given. Comparison is also performed between the proposed multilevel inverter and several conventional seven-level inverters. The proposed multilevel inverter is simulated in MATLAB/Simulink environment under grid-tied transformer-less operation. The experimental 210 VA prototype confirms the correctness of the given theories and the correct operation of the proposed topology.